2014
DOI: 10.1097/igc.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Curative Pelvic Exenterations in Patients With Recurrent Uterine Cervical or Vaginal Cancer

Abstract: The presence of vascular emboli is a new prognostic factor in cases of recurrent cervical or vaginal cancer. Assessing the presence of vascular emboli on pretherapeutic biopsies could facilitate the selection of patients eligible for curative pelvic exenterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…However, contradictory data have been reported. For example, in a series of total pelvic exenteration for recurrent gynecological cancer, Sardain et al16 and Mourton et al17 reported that the rate of mesorectal nodal metastasis was 19% and 10%, respectively. They also found that MRNM is common in patients with rectal wall involvement in recurrent cervical cancer as well as ovarian cancer 18.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory data have been reported. For example, in a series of total pelvic exenteration for recurrent gynecological cancer, Sardain et al16 and Mourton et al17 reported that the rate of mesorectal nodal metastasis was 19% and 10%, respectively. They also found that MRNM is common in patients with rectal wall involvement in recurrent cervical cancer as well as ovarian cancer 18.…”
Section: Discussionmentioning
confidence: 99%
“…The median time of recurrence, after initial treatment, is 18-24 months and occurs in 20%-30% of patients initially treated with concomitant chemotherapy for recurrent cervical cancer [18]. The overall limitation of the existing studies is the heterogeneity in the inclusion criteria and the consideration of several types of cancers (of the cervix, endometrium, vulva, and ovaries) [19]. A 5-year survival of 46% for primary advanced and 17% for locally recurrent rectal cancer has also been shown [20].…”
Section: Outcome and Prognosismentioning
confidence: 99%
“…The 5-year survival rates of patients who undergo total pelvic exenteration range from 20 to 60% [12,13,14]. Clearly, exenteration is a major surgical procedure and is associated with a procedure-associated mortality of up to 10% [12,13,14,15,16,17,18]. Therefore, extensive counselling of patients is necessary before undergoing this treatment.…”
Section: Treatment Of Local Pelvic Recurrencementioning
confidence: 99%
“…A systematic review of the literature of the Cochrane Collaboration identified no randomized trial and concluded that there is no evidence to inform decisions about exenterative surgery for women with recurrent gynecologic malignancies [19]. Sardain et al [18] performed pelvic exenterations in 13 women with recurrent cervical cancer and 3 women with recurrent vaginal cancer. All of the patients had received pelvic irradiation before; the median tumor size was 4.3 cm.…”
Section: Treatment Of Local Pelvic Recurrencementioning
confidence: 99%
See 1 more Smart Citation